A Research Agenda to Advance Pediatric Emergency Care Through Enhanced Collaboration Across Emergency Departments. (27th November 2018) - Barata, Isabel; Auerbach, Marc; Badaki‐Makun, Oluwakemi; Benjamin, Lee; Joseph, Madeline M.; Lee, Moon O.; Mears, Kim; Petrack, Emory; Wallin, Dina; Ishimine, Paul; Denninghoff, Kurt R.
Abstract: In 2018, the Society for Academic Emergency Medicine and the journal Academic Emergency Medicine ( AEM ) convened a consensus conference entitled, " Academic Emergency Medicine Consensus Conference: Aligning the Pediatric Emergency Medicine Research Agenda to Reduce Health Outcome Gaps." This article is the product of the breakout session, "Emergency Department Collaboration‐Pediatric Emergency Medicine in Non‐Children's Hospital"). This subcommittee consisting of emergency medicine, pediatric emergency medicine, and quality improvement (QI) experts, as well as a patient advocate, identified main outcome gaps in the care of children in the emergency departments (EDs) in the following areas: variations in pediatric care and outcomes, pediatric readiness, and gaps in knowledge translation. The goal for this session was to create a research agenda that facilitates collaboration and partnering of diverse stakeholders to develop a system of care across all ED settings with the aim of improving quality and increasing safe medical care for children. The following recommended research strategies emerged: explore the use of technology as well as collaborative networks for education, research, and advocacy to develop and implement patient care guidelines, pediatric knowledge generation and dissemination, and pediatric QI and prepare all EDs to care for the acutely ill and injured pediatric patients. In conclusion, collaboration between general EDs and academic pediatric centers on research, dissemination, and implementation of evidence into clinical practice is a solution to improving the quality of pediatric care across the continuum.